Genetic Differentiations among the Populations of Salvia japonica (Lamiaceae) and Its Related Species - SUDARMONO SUDARMONO; HIROSHI OKADA (Bogor Agricultural University, Indonesia, 2008)
Morphological and genetic variations within Salvia japonica (Lamiaceae) and its related species in Japan were analyzed for clarifying their taxonomic significance. The genetic variations were explored through chloroplast and nuclear ribosomal DNA sequences and allozyme polymorphisms. Since chromosome numbers characterized the genus of Salvia, we also examined whether the karyotypes were different. We examined 58 populations of S. japonica and 14 populations of others species of Salvia. Among the populations of S. japonica represented four forms (f. japonica, f. longipes, f. lanuginosa and f. albiflora). The size of chromosomes were various among Salvia spp. Based on the allozyme as well as the DNA sequence, the populations of S. japonica separated from the others Salvia species. The populations of S. japonica exhibited four combinations of the morphological characters. However, these combinations did not correlate to the four forms of S. japonica. In addition, the morphological variations did not correlate to the allozyme and DNA sequences. It is suggested that the four morphological variations as well as the four form of S. japonica should not considered to be a taxonomic unit; accordingly, S. japonica were considered to be still at the early stage of speciation process. Key words: allozyme, DNA, morphological variations, Salvia japonica